Serum vitamin D Levels in overweight and obese children and adolescents (Research, Society and Development, 2020)
The present study aimed to verify vitamin D levels in overweight and obese children and adolescents. This is a cross-sectional study, conducted with children and adolescents aged 6 to 18 years duly enrolled in municipal schools in a city of Maranhão. Serum vitamin D levels were evaluated in 9 children and adolescents, where an average value of 28.8 ng / ml (SD ± 5.73) was observed among the study participants, characterizing it as insufficient according to the value. established reference However, when comparing serum levels between genders, it was found that males (30.26ng / ml ± 4.3) had higher vitamin levels than females (26.05ng / ml ± 7.07)). When the values of serum levels obtained in the study were classified, it was observed that most were in the range of insufficiency and sufficiency of vitamin D, both with 44.4%. Regarding the insufficiency of the vitamin between the sexes, it was found that the male and female had an equal percentage (22.2%).